Pyroptosis is a critical immune-inflammatory response involved in atherosclerosis - He, Xiao; Fan, Xuehui; Bai, Bing; Lu, Nanjuan; Zhang, Shuang; Zhang, Liming (Pharmacological research, 2021)
[Display omitted] Pyroptosis is a form of programmed cell death activated by various stimuli and is characterized by inflammasome assembly, membrane pore formation, and the secretion of inflammatory cytokines (IL-1β and IL-18). Atherosclerosis-related risk factors, including oxidized low-density lipoprotein (ox-LDL) and cholesterol crystals, have been shown to promote pyroptosis through several mechanisms that involve ion flux, ROS, endoplasmic reticulum stress, mitochondrial dysfunction, lysosomal rupture, Golgi function, autophagy, noncoding RNAs, post-translational modifications, and the expression of related molecules. Pyroptosis of endothelial cells, macrophages, and smooth muscle cells in the vascular wall can induce plaque instability and accelerate atherosclerosis progression. In this review, we focus on the pathogenesis, influence, and therapy of pyroptosis in atherosclerosis and provide novel ideas for suppressing pyroptosis and the progression of atherosclerosis.